Assessing the welfare impacts of changes in recreational fisheries management: A modelling approach for European sea bass. (February 2023) - Cevenini, Fabio; Andrews, Barnaby; Muench, Angela; Lamb, Philip; Ferrini, Silvia; Hyder, Kieran
Abstract: Economic appraisal of the impacts of fisheries policies is a legal requirement in many global fisheries and is crucial for effective policy making. Some changes in costs and benefits attributable to policy can be assessed through impacts on markets, whilst others are more difficult, as markets may not exist. Analysis is needed to assess value generated by fisheries under different management regimes. The northern stock of European sea bass ( Dicentrarchus labrax ) has declined rapidly over the past decade leading to management of both the commercial and recreational sectors. Bag limits, closed seasons, and minimum sizes were introduced for recreational fishers, but the social impact of management measures has not been quantified. Here, we use sea bass to demonstrate a method for assessing the impact of management measures on recreational fisher welfare. Through combining stock assessments, individual catch data, and estimates of welfare from a recent choice experiment, differences in welfare under a range of regulatory scenarios were compared. Nine scenarios based on management implemented between 2014 and 2020 were tested. Highest welfare estimates were found with the lowest levels of restrictions and lowest estimates for a no-take fishery, which was driven by retained fish having a higher value than released fish. There was a difference of £ 22.03 million in estimated welfare generated by the recreational sector between these extremes, with the remaining scenarios amid those values. Our results highlight the need for policy makers to carefully consider management options that protect both fish stocks and the welfare of recreational fishers. Highlights: An interdisciplinary approach is necessary to balance exploitation and social welfare. Quantifying recreational fishers' welfare is central to assessing the impact of fishery policies. Differences in welfare estimates between the most and the least valuable sea bass management strategies was £ 22.03 million. The length of season generated the greatest impact on sea bass recreational fishers' welfare. The results are dependent on current stock structure and catches, so should be updated as the stock recovers.